Translation of Culture-Specific-Items in religious texts : a case study of the Noble Qur’an - Ayyad, Ghada Rajeh; Obeidat, Adham; Tengku Sepora Tengku Mahadi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Translation of cultural terms is considered one of the difficulties that translators face in translating the Noble Qur’an. The task of translating cultural terms becomes more complicated and difficult when dealing with such a sensitive text. A variety of procedures are suggested to be used to overcome this problem. This study aims to investigate the translation procedures used by the translators of the Noble Qur’an to translate Culture-Specific-Items (CSIs) from Arabic into English and to identify the most frequent used procedure. This study is a descriptive qualitative one. It falls under the category of product-oriented study that deals with description of translations, comparative description of several translations of the source text and description of larger corpora of translation. The CSIs are collected from Al-Ma’idah Chapter in the Noble Qur’an and its English translation by Abdullah Yusuf Ali (1983). The meanings of the CSIs are taken from The Dictionary of Islamic Words and Expressions by Saleh (2011). The authors analyzed and investigated the translations of these CSIs and identified the procedures used by the translator. The study finds that the translator used 10 translation procedures to translate culture- specific- items. These procedures are functional equivalent, cultural equivalent, modulation, borrowing, definition, generalization, description, footnotes and explicitation. It also finds that the most frequent used procedure by the translator is the definition. Moreover, the less used procedures are the generalization and explicitation. By discussing the procedures used to translate the CSIs in the Noble Qur’an, translators may get helpful information about choosing the suitable procedure in their translations to achieve proper translation.